Solar cogeneration for processes in the food industry - De Montreuil Estupiñan, Christian André (2019)
In this paper, the technical, financial and legal feasibility of employing solar cogeneration for the food industry sector in Peru will be demonstrated. In consequence, we will quantify the electric and thermal energy obtained from a conventional Rankine cycle, with the particularity that the water used to condense the steam that exits the turbine will be employed for the required processes in the industrial plants, because of the high temperature obtained from the heat exchange with the steam. In addition, we will detail the processes in which the obtained energy will be employed, the quantity of devices to be used in this system, as well as the required specifications and the thermodynamic parameters, for a proper operation of the cogeneration system. Moreover, we will prove the legal feasibility of choosing a solar cogeneration system in the Peruvian legal system, and, in view of the relevance of this project, we will propose an administrative and legal scheme through which it can be accomplished. In this respect, the project is interdisciplinary, because it involves the combination of legal and engineering approaches.